2011
DOI: 10.1021/jp2001332
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Aqueous Micellar Gels of a Thermo- and pH-Sensitive ABA Triblock Copolymer

Abstract: This article presents a systematic study of the effect of pH on the rheological properties of aqueous micellar gels formed from 10.0 wt % aqueous solutions of a thermo- and pH-sensitive ABA triblock copolymer, poly(ethoxydi(ethylene glycol) acrylate-co-acrylic acid)-b-poly(ethylene oxide)-b-poly(ethoxydi(ethylene glycol) acrylate-co-acrylic acid) (P(DEGEA-co-AA)-b-PEO-b-P(DEGEA-co-AA)). The block copolymer was synthesized by atom transfer radical polymerization of DEGEA and tert-butyl acrylate with a molar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 80 publications
(172 reference statements)
3
86
1
Order By: Relevance
“…The PDIs of the triblock copolymers PMH7, PMH8 and PMH9 are 1.454, 1.230 and 1.276, respectively ( Table 1). The PDI indicates that the polymerization was well controlled [14,15].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The PDIs of the triblock copolymers PMH7, PMH8 and PMH9 are 1.454, 1.230 and 1.276, respectively ( Table 1). The PDI indicates that the polymerization was well controlled [14,15].…”
Section: Resultsmentioning
confidence: 98%
“…These thermosensitive micellar gels had been investigated for applications in controlled release of substances and tissue engineering because of their unique thermoinduced in situ sol-gel transition and the nature of physical cross-linking. (2) If the A block is permanently water soluble and B block is thermosensitive exhibiting an LCST in water, the polymer molecules self-assemble into discrete, often spherical, micelles at temperatures above the LCST and the sol-gel transition is brought about by the packing of micelles into an ordered structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lutz et al [11][12][13] reported a new class of water-soluble copolymers based on 2-(2-methoxyethoxy) ethyl methacrylate (MEO 2 MA). It has been confirmed that these copolymers can be considered as potential candidates for application in biotechnology [14][15][16]. In spite of these advantages, intermolecular interactions are too weak to form crosslinking gel upon heating-induced phase transition for MEO 2 MA [17].…”
Section: Introductionmentioning
confidence: 94%
“…To further study the sol-gel transition and rheological properties of copolymer solutions, we recorded the dynamic moduli (G′ and G″) of copolymer solutions at various temperatures [16,32]. Figure 9 shows the data from an oscillatory shear measurement of the 10.0 wt% aqueous solutions.…”
Section: Thermoresponsive Behaviors Of Triblock Copolymer Solutionsmentioning
confidence: 99%
“…The gelation kinetics of physical micellar gels depends on the strength and number density of physical crosslinks [105,107]. The gelation kinetics of covalently-bonded chemical gels depends on several factors including the concentration and distribution of crosslinkable groups and initiator [104,[108][109][110].…”
Section: Gelation Timementioning
confidence: 99%